Assessment and Management of Cognitive and Psychosocial Dysfunctions in Patients With Major Depressive Disorder: A Clinical Review - Fiorillo, Andrea; Carpiniello, Bernardo; De Giorgi, Serafino; La Pia, Silvestro; Maina, Giuseppe; Sampogna, Gaia; Spina, Edoardo; Tortorella, Alfonso; Vita, Antonio (Frontiers in Psychiatry, 2018)
Background: Full functional recovery, is defined as a state in which patients are again able to enjoy their usual activities, return to work, and take care of themselves, and it should represent the end goal of treatment in patients with major depressive disorder (MDD). Patients with MDD report many unmet needs, including residual cognitive symptoms, lack of improvement in psychosocial functioning and life satisfaction, even during mood symptom remission. In this paper, we aim to: a) identify the available assessment tools for the evaluation of cognitive and psychosocial functioning in patients with MDD; b) provide an overview of therapeutic options that can improve full functional recovery in MDD also by improving of cognitive symptoms. Methods: The relevant databases MEDLINE, ISI Web of Knowledge - Web of Science Index, Cochrane Reviews Library and PsychoINFO were searched for identifying papers on validated tools for the assessment of cognitive and personal functioning in patients with MDD. Results: New assessment tools (such as the THINC-it TOOL, the COBRA, the SCIP-D and the UPSA-D) have been developed for evaluating the cognitive dysfunction in MDD patients. Adopting these tools in the clinical routine practice is useful to evaluate the improvement in cognitive functioning and, therefore, the achievement of full functioning recovery. The optimal management of patients with MDD include the combination of pharmacological compounds and psychosocial interventions for achieving full functional recovery in patients with MDD. Conclusions: Full functional recovery must be the target of any treatment programme for patients with MDD. In order to achieve this goal, it is necessary to develop personalized treatment and integrate psychosocial and psychopharmacological interventions.